The Pic Coustic Band’s Performance at a Worship Service at the GKJW Congregation in Surabaya - Jesisca Hardani (Universitas Negeri Surabaya, 2026)
The Pic Coustic band is one of the bands based at the Jawi Wetan Christian Church Congregation in Surabaya. This study aims to explain the existence of the Pic Coustic band and the factors that support its existence at the Jawi Wetan Christian Church Congregation in Surabaya. This study employs a qualitative descriptive approach. The data collection techniques used include observation, interviews, and documentation. The results of this study are: (1) The existence of the Pic Coustic band is based on its activities and factual evidence; (2) The factors supporting the existence of the Pic Coustic band include external factors such as the community and social media, while internal factors include cooperation among members toward a common goal, distinctive characteristics, and performance experience.